P128 INHIBITION OF INTESTINAL EPITHELIAL CELL PYROPTOSIS AND ASSOCIATED MUCOSAL BARRIER DEFECTS IS A POTENTIAL THERAPEUTIC MECHANISM OF ACTION FOR MESALAMINE IN IBD. (7th February 2019) - Davis, Elisabeth M; Zhang, Di; Glover, Sarah C; Stappenbeck, Thaddeus; Wang, Shanzhi; Liu, Julia J
Abstract: Background: Mucosal barrier dysfunction to luminal microbes plays a crucial role in the development of intestinal inflammation in inflammatory bowel disease (IBD). Recently, intestinal epithelial cell (IEC) death resulting from a form of innate immune activation called pyroptosis was proposed as a possible cause of this barrier defect. We hypothesize that inhibition of IEC pyroptosis and prevention of associated barrier defects is a potential mechanism of action for mesalamine. The aim of this study was to determine the effect of mesalamine on recombinant caspase-1 enzyme activity, in vitro cell and spheroid IEC culture model undergoing pyroptosis and in IBD patients treated with mesalamine. Methods: Recombinant caspase-1 enzyme activity was examined using the specific caspase-1 inhibitor Acetyl-YVAD-Amino-4-methylcoumarin (Ac-YVAD-Amc) as the substrate to generate Lineweaver–Burk plots. An end-point assay detecting cleavage of gasdermin D confirmed the results. Polarized T84 monolayers and spheroids isolated from the colon of an EGFP-actin mouse were used to study pyroptosis in vitro using nigericin (N) as an inflammasome inducer. YVAD and mesalamine (MES) were used to inhibit pyroptotic cell death in vitro . Epithelial barrier function was assessed by measuring trans-epithelial resistance (TER) of T84 monolayers. Time-lapsed confocal imaging was performedto assess the epithelial integrity in the spheroid culture model. IEC pyroptosis on mucosal biopsy samples from patients before and after mesalamine therapy were quantitated with immunohistochemical staining for activated caspase-1 and were compared using Wilcoxon signed rank test. Results: Mesalamine inhibited recombinant caspase-1 enzyme activity in a non-competitive manner. Consistently, mesalamine reduced the rate of cleavage of gasdermin D. Time-lapsed imaging of the spheroids grown in matrigel revealed pyroptotic IEC death resulted in transient breaches between pyroptotic IECs in the epithelial lining of spheroid. These breaches permitted entry of 40kDa FITC-dextran into the center of the spheroid. In T84 monolayers, MESinhibited pyroptotic-mediated barrier dysfunction and maintained epithelial integrity with equal potency as YVAD, as measured by TER (75 ± 2.2% N alone, 96 ± 1.2% N+YVAD, 97 ± 2.6% N+MES; P<0.01). Quantitation of mucosal biopsy samples from 7 ulcerative colitis (3M, 4F) and 4 Crohn's disease (1M, 3F) patients revealed a significant reduction in the IEC pyroptosis: the median pre-treatment biopsy pyroptosis was 16 (10, 25) caspase-1 positive cells per 1000 IECs versus 9 (0, 18) positive cells/1000 IECs (p=0.029) on mesalamine. Conclusions: Our results indicate that mesalamine is a direct, non-competitive inhibitor of caspase-1 enzyme, and inhibition of IEC pyroptosis and associated mucosal barrier defects may be a therapeutic mechanism of action for mesalamine in IBD treatment.